Demanda de productos y servicios microfinancieros para microempresarios de la ciudad de Loja, año 2014 - Gonzaga Torres, Karen Alina. (2015)
The present work of end of qualifications executed with the aim to realize an analysis of the products and microfinancial services that there demand the microbusinessmen of Loja's city, in order to determine if the offer of the diverse operators of microfinance as Cooperatives of Saving and Credit, adjusts to the royal needs of the microbusinessmen, for which appeared a survey applied to 374 microbusinessmen, distributed according to his economic activity; of equal way an interview was realized to 17 Coacs regulated by the Superintendence of Popular and Solidary Economy to determine his offer. Giving place to the diagnosis of results and comparative analysis between offer and demand, being the microcredit the product with major demand, since 9 of every 10 microbusinessmen have acceded to this type of financing that has managed in certain way to cover his micromanagerial needs. To understand the way in which the microbusinessmen interact with the products and services of microfinance will help to the institutions to evolve or modify his products as response to the preferences and needs of the same ones.